A companion to ancient Near Eastern languages - Hasselbach, Rebecca (Blackwell companions to the ancient world, 2020)
"The current volume serves as an introduction to a representative sample of Ancient Near Eastern languages and language families attested during the time period of roughly 3200 BCE to the second century CE. This time-frame reflects the time from the beginning of writing (around 3200 BCE) to the end of cuneiform writing in the second century CE. The geographical scope selected reaches from Egypt through the Levant, Anatolia, northern Syria, Mesopotamia, all the way to southern Arabia and thus reflects all major cultures attested in the Ancient Near East during this time period. Although it was impossible to include a description of all languages attested in this wide geographical area throughout more than three millennia due to limitations in space, at least most language families are represented, such as Egyptian, Sumerian, Semitic, Indo-European, Elamite, and Hurrian"--